Effect and safety of sivelestat on acute severe pancreatitis with systemic inflammatory response syndrome: a retrospective study - Jiafeng Xie; Ruyi Lei; Hui Pei; Yulei Gu; Luanluan Zhang; Jingrong Liu; Yahui Huang; Yepeng Zhang; Yanan Zi; Changju Zhu; Zhiqiang Zhu (Scientific Reports)
Abstract The study was to explore the efficacy and safety of sivelestat (SV) in the treatment of severe acute pancreatitis (SAP) with systemic inflammatory response syndrome (SIRS). A total of 102 SAP patients diagnosed and treated in the Emergency Intensive Care Unit of the First Affiliated Hospital of Zhengzhou University from January 2021 to August 2024 were selected. The changes of disease outcome, hospital stays and mortality were compared between the two groups. A total of 102 patients were recruited to control group (n = 56) or SV group (n = 46) according to whether SV was applied or not. There was no significant difference in baseline data at admission between the two groups. After 1 week of treatment, all the indexes in both groups improved. The duration of ventilator use (p = 0.0400) and ICU stays (p  = 0.0495) in SV group was shorter than that in control group, but there was no significant difference in mortality between the two groups. Although SV did not reduce the mortality of patients with SAP, it reduced the length of ventilator use and ICU stay.